Marketing management : (McGraw-Hill/Irwin, 2005)
Marketing Management, 5/e by Mullins, Walker, Boyd, and Larreche is specifically designed for courses in which decision-focused cases are an important element and/or where student projects, such as the development of a marketing plan, are assigned. The concentration on strategic decision making sets this book apart from other texts that place greater emphasis on description of marketing phenomena than on the strategic and tactical marketing decisions that managers and entrepreneurs must make each and every day. This edition continues to be the most current and internet-savvy book available, injecting the latest developments in internet-based communication and distribution technology into every chapter. Also, an entire chapter (Chapter 15) is devoted to the development of marketing strategies for the new economy. The author team;s rich entrepreneurial, marketing management, and consulting experience spanning a broad variety of manufacturing, service, software, and distribution industries provides an abundance of real-world, global perspectives.